Are Spanish Students Customers? Paradoxical Perceptions of the Impact of Marketisation on Higher Education in Spain. (March 2021) - Jayadeva, Sazana; Brooks, Rachel; Gupta, Achala; Abrahams, Jessie; Lažetič, Predrag; Lainio, Anu
This article examines how higher education (HE) students are conceptualised in Spain, drawing on an analysis of policy and institutional narratives about such students, as well as on the perspectives of university staff and students themselves. More specifically, it will explore an interesting paradox that we encountered in our data: on one hand, marketisation is less firmly established in the HE system of Spain than in many other European countries, and policy and institutional narratives in Spain present the HE system as being relatively unmarketised. On the other hand, the staff and students we interviewed presented the Spanish HE system and the student experience as having been dramatically transformed by marketisation. In analysing this paradox, the article highlights the importance of not viewing countries as coherent educational entities. In addition – while broadly supporting scholarship that has pointed to a growing market orientation of national HE systems across Europe – the article draws attention to how the manner in which the marketisation of HE is experienced on the ground can be very different in different national contexts, and may be mediated by a number of factors, including perceptions about the quality of educational provision and the labour market rewards of a degree; the manner in which the private cost of education (if any) is borne by students and their families; and the extent to which marketisation may have become entrenched and normalised in the HE system of a country.